2017
DOI: 10.1136/gutjnl-2016-313432
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of ethanol-induced Akkermansia muciniphila depletion ameliorates alcoholic liver disease

Abstract: Ethanol exposure diminishes intestinal abundance in both mice and humans and can be recovered in experimental ALD by oral supplementation. promotes intestinal barrier integrity and ameliorates experimental ALD. Our data suggest that patients with ALD might benefit from supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
364
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(415 citation statements)
references
References 57 publications
20
364
2
4
Order By: Relevance
“…The widespread nature of these microbial changes reflects the profound impact of alcohol despite the very skewed baseline of cirrhosis. While we specifically excluded patients with alcoholic hepatitis, prior studies have demonstrated a similar dysbiosis in their stool (Grander et al., ). We extend that data by defining changes in the mucosal microbial composition and come to an interesting conclusion that dysbiotic changes similar to that found with alcoholic hepatitis are already present in patients who are prone but have not developed it yet.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread nature of these microbial changes reflects the profound impact of alcohol despite the very skewed baseline of cirrhosis. While we specifically excluded patients with alcoholic hepatitis, prior studies have demonstrated a similar dysbiosis in their stool (Grander et al., ). We extend that data by defining changes in the mucosal microbial composition and come to an interesting conclusion that dysbiotic changes similar to that found with alcoholic hepatitis are already present in patients who are prone but have not developed it yet.…”
Section: Discussionmentioning
confidence: 99%
“…Collective findings have confirmed that the action of A. muciniphila could extend to various hepatic disorders such as fatty liver disease, hepatic inflammation, and hypercholesterolemia. Oral supplementation of A. muciniphila can restore A. muciniphila depletion caused by ethanol exposure in mice, preventing the liver from alcoholic injury, neutrophil infiltration, and steatosis (Grander et al, 2018). In a concanavalin A-induced liver injury mouse model, oral administration of A. muciniphila reduced serum Alanine Aminotransferase (ALT) and Aspartate Aminotransferase (AST) and alleviated liver damage (Wu et al, 2017).…”
Section: The Causative Role Of Akkermansia Muciniphila In Liver Disormentioning
confidence: 99%
“…A. muciniphila treatment restored epithelial tight junction proteins (claudin-3 and occludin) in colonic epithelial cells to defend against the invasion of ethanol. The evidence suggests that A. muciniphila has protective actions against alcoholic liver disease focusing on the intestine (Grander et al, 2018). Moreover, the interference of A. muciniphila in improving intestinal barrier function is evoked by improving occludin and Tjp-1 expressions and suppressing LPS production followed by increasing the variety and volume of gut microbes (Wu et al, 2017).…”
Section: The Causative Role Of Akkermansia Muciniphila In Liver Disormentioning
confidence: 99%
“…Although Akkermansia muciniphila were considered beneficial to mucin turnover [6], its overgrowth may also compromise the colonic integrity and enhance the enteric permeability. As results, gut microbes or their components such as lipopolysaccharide (LPS) can simply trespass the colonic barrier and enter the blood circulation to trigger immune activation and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%